Economic Growth and Income Inequality Relationship: Role of Credit Market Imperfection (The Pakistan Development Review, 2008)
The 20th century has witnessed unequalled success in improving the living standard of people in most part of the world. According to World Bank annual Statistical reports, poverty has declined significantly in developing countries over the past twenty years but the progress has been uneven. The number of people living in poverty fell from 1.5 billion in 1981 to 1.1 billion in 2001. However, many low-income developing countries are still trapped in vicious circle of poverty. In Sub-Saharan Africa, the number of poor rose from 41 percent to 46 percent between 1981 to 2001.While in Eastern Europe and Central Asia, the numbers of poor people have risen to around 20 percent in 2001.1 Therefore; reduction of widely scattered poverty is the most challenging goal for low income developing countries. Economic growth is considered to be a powerful force for reducing poverty. High and sustained economic growth increases the labor demand and wages which in return will reduce poverty. Similarly, better earnings as a result of reduction in poverty lead to increase productivity and growth. But the extent of poverty reduction as a result of economic growth depends on how the distribution of income changes with economic growth and on initial Inequalities in income. If income inequality increases, then economic growth does not lead to a significant poverty reduction. Many developing countries achieved high growth rates in different periods but poverty does not reduce significantly in these periods due to increase in income inequalities. Most South and East Asian economies grew at higher per capita rates since early 1970 along with rise in income inequality over time. In contrast, Latin American countries grew by less than the half of average growth rates in South and East Asia while maintaining high income inequality.2 The differences in income inequality at a given rate of growth require that efforts to reduce poverty by stimulating growth are not sufficient and need to be complemented by efforts to reduce income inequalities.